2016
DOI: 10.1155/2016/4087632
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cardiomyopathy: A Current View on the Pathophysiology, Diagnosis, and Treatment

Abstract: Inflammatory cardiomyopathy is defined as inflammation of the heart muscle associated with impaired function of the myocardium. In our region, its etiology is most often viral. Viral infection is a possible trigger of immune and autoimmune mechanisms which contributed to the damage of myocardial function. Myocarditis is considered the most common cause of dilated cardiomyopathy. Typical manifestation of this disease is heart failure, chest pain, or arrhythmias. The most important noninvasive diagnostic method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
65
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 103 publications
0
65
0
12
Order By: Relevance
“…In rat and mouse models, several studies had addressed the efficacy of sirolimus to the improvement in cardiac function through the activation of autophagy [2,12]. Xie et al [12] strictly defined a rat iDCM model immunized with cardiac-specific peptides combined with a nonspecific adjuvant agent [12,13]. It is reported that sirolimus improved the cardiac function (i. e., ejection fraction) in a dose-dependent manner in the two groups treated with 1 and 2 mg/kg sirolimus intraperitoneally injected for 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rat and mouse models, several studies had addressed the efficacy of sirolimus to the improvement in cardiac function through the activation of autophagy [2,12]. Xie et al [12] strictly defined a rat iDCM model immunized with cardiac-specific peptides combined with a nonspecific adjuvant agent [12,13]. It is reported that sirolimus improved the cardiac function (i. e., ejection fraction) in a dose-dependent manner in the two groups treated with 1 and 2 mg/kg sirolimus intraperitoneally injected for 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that sirolimus has therapeutic effects against human iDCM. Krejci J et al [28] suggested that immunosuppressive or antimicrobial treatment should be considered in some cases depending on the results of endomyocardial biopsy; moreover, the persistence of severe left ventricular dysfunction may necessitate the use of device therapy. Recently, Maisch et al [29] reviewed the treatment options for iDCM and summarized that immunosuppressive treatment has proven to be beneficial in the TIMIC and ESETCID trials.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation, especially sustained low-grade inflammation, is considered to be a major prelude to diseases such as diabetes, cardiovascular diseases, and most importantly, cancer. [1][2][3] Since, inflammation is part of the innate immune response, modulation of the immune system is thought to be a key event in the pathogenesis of inflammation-associated diseases. 4,5 The effects of microbial components on thymocytes have been examined in the context of regulation of T-cell response during bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most frequent causes of DCM in young children is myocarditis or inflammation of the heart muscle, which can be caused by various conditions, including viral or bacterial pathogens, autoimmune disease or exposure to toxins [4]. The most common viral causes of myocarditis in the paediatric population include coxsackievirus B3, adenovirus, herpesvirus, parvovirus, influenza A and B, and hepatitis viruses [5][6][7][8]. Myocarditis is also detected during post mortem in 2-46 % cases of sudden death in young people [2,3].…”
Section: Introductionmentioning
confidence: 99%